Pengaruh Literasi Keuangan dan Modal Usaha terhadap Keberhasilan Usaha UMKM Kuliner Kecamatan Medan Selayang - Viona Lira Agustania; Nindya Yunita; Alfifto Alfifto (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of financial literacy and business capital on the business success of culinary MSMEs in Kecamatan Medan Selayang. A quantitative approach is used in this study to determine the magnitude of the influence of independent variables on the dependent variable. The population in this study consists of culinary MSME entrepreneurs in Kecamatan Medan Selayang in 2025, totaling 102 entrepreneurs. The sampling technique used is saturated sampling (sampling jenuh), in which all members of the population are used as the sample, resulting in a sample size of 102 respondents. Data analysis is conducted using SPSS with multiple linear regression analysis to determine the influence of independent variables on the dependent variable. The results of the study indicate that the Financial Literacy variable has a positive and significant influence on business success. This is evident from the significant value (0.000) < 0.05 and the beta value of 0.412. The Business Capital variable has a positive and significant influence on business success. This is evident from the significant value (0.000) < 0.05 and the beta value of 0.522. Business Capital has a more dominant influence than Financial Literacy in affecting the business success of culinary MSMEs in Kecamatan Medan Selayang. Simultaneously, Financial Literacy (X1) and Business Capital (X2) together significantly influence the business success of culinary MSMEs in Kecamatan Medan Selayang.